FRI0197 Time Lag of Improvement in Synovial Hypertrophy Compared To Rapid Response in Power Doppler Synovial Vascularity in Post-Adalimumab Rheumatoid Arthritis. (15th July 2016) - Chen, Y.-C.; Chen, J.-F.; Cheng, T.-T.
Abstract : Background: In previous studies, the patients achieved greater disease control by adalimumab at 24 weeks, this response was maintained over the next 24 weeks 1, however, we could not found the characteristic in image to confirm the clinical presentations. Objectives: This study aimed to validate the use of power Doppler ultrasonography (PDUS) for evaluating synovial vascularity and synovial hypertrophy for synovitis in patients with rheumatoid arthritis (RA) treated with adalimumab. Methods: The synovial disease activity and vascularity of RA on both wrists (radio-carpal joint) were assessed using GS and PDUS to derive the composite US scores based on abnormal counts and severity. The relationship between each measure was determined. Results: The 71 patients who received adalimumab therapy had significantly decreased DAS28, ESR, and CRP. After one month, PD score decreased and then remained low for 12 months. Synovial hypertrophy did not change until 3–6 months after, when it started to improve ( p =0.017). By multivariate analysis, sex, age, BMI, and DAS28 did not lead to any difference between synovial hypertrophy and PDUS changes ( p =0.498). Conclusions: Composite US markers of synovial hypertrophy correlate significantly to the DAS28 score and ESR/CRP in adult RA. The time needed for synovial hypertrophy to decrease may be up to 3–6 months after adalimumab therapy. Using ultrasound Doppler measurements predict success of treatment with anti-TNF-alpha has been a trend in monitoring biological therapy in patients with RA References: Keystone EC, et al. Arthritis and rheumatism. May 2004;50(5):1400–1411. Disclosure of Interest: None declared